A single-arm Phase II validation study of preventing oxaliplatin-induced hypersensitivity reactions by dexamethasone: the AVOID trial - Yoshida Y; Hirata K; Matsuoka H; Iwamoto S; Kotaka M; Fujita H; Aisu N; Hoshino S; Kosaka T; Maeda K; Kiyomi F; Yamashita Y (Dove Medical Press, 2015)
Yoichiro Yoshida,1 Keiji Hirata,2 Hiroshi Matsuoka,3 Shigeyoshi Iwamoto,4 Masahito Kotaka,5 Hideto Fujita,6 Naoya Aisu,1 Seiichiro Hoshino,1 Takeo Kosaka,6 Kotaro Maeda,3 Fumiaki Kiyomi,7 Yuichi Yamashita1 1Department of Gastroenterological Surgery, Fukuoka University Faculty of Medicine, Fukuoka, Japan; 2Department of Surgery, Fukuoka Sanno Hospital, Fukuoka, Japan; 3Department of Surgery, Fujita Health University School of Medicine, Toyoake, Japan; 4Department of Surgery, Kansai Medical University Hirakata Hospital, Osaka, Japan; 5Gastrointestinal Cancer Center, Sano Hospital, Kobe, Japan; 6Department of Surgical Oncology, Kanazawa Medical University, Uchinada, Japan; 7Academia, Industry and Government Collaborative Research Institute of Translational Medicine for Life Innovation, Fukuoka University, Fukuoka, Japan Background: Patients with colorectal cancer treated with oxaliplatin are at risk of hypersensitivity reactions, with the incidence estimated to be 12%–20%. Coinfusion of dexamethasone and oxaliplatin could potentially reduce the incidence of these reactions, but oxaliplatin is reported to be incompatible with alkaline compounds in solution. However, in a previous retrospective study we found that the pH of a solution of dexamethasone and oxaliplatin was less than 7.4, and that hypersensitivity to oxaliplatin could have been prevented by coinfusion of dexamethasone. We aimed to evaluate the effectiveness of coinfusion of dexamethasone and oxaliplatin to prevent oxaliplatin-induced hypersensitivity reactions.Patients and methods: The AVOID trial was a prospective, multicenter, open-label, single-arm Phase II trial conducted from January to September 2013. The study included 73 patients who received capecitabine plus oxaliplatin (XELOX) or XELOX plus bevacizumab therapy for colorectal cancer. In all patients, oxaliplatin was administered in combination with dexamethasone. The primary outcome measure was the presence of hypersensitivity reactions.Results: Hypersensitivity reactions occurred in three patients (4.1%); all three experienced a cutaneous reaction (grade 1 erythema). None of the 73 patients developed respiratory symptoms, ocular symptoms, or anaphylaxis. Grade 3 or higher hemotoxicity occurred in 13.7% of the patients and grade 3 or higher nonhematological toxicity occurred in 13.7%. The response rate to treatment was 64.4%.Conclusion: The coinfusion of dexamethasone and oxaliplatin effectively reduced oxaliplatin-induced hypersensitivity reactions in patients with colorectal cancer. This approach should be considered for all patients treated with oxaliplatin, allowing treatment to be completed as planned. Keywords: oxaliplatin, dexamethasone, hypersensitivity, allergy